The Relations between Birth Weight and The Growth of Children under Five in Puskesmas Goarie Subdistrict Marioriwawo Regency Soppeng - Kadek Ayu Erika; Mulhaeriah Mulhaeriah; Nurul Arifah Amir (Indonesian Contemporary Nursing Journal, 2019)
Introduction:The birth weight is one of health assessment and prediction of children under five in the future. Growth assessment can uses Denver II screening test to detect earlier the growth whether normal or it risks to delay in growing to know the relations between birth growth and children under five growth in Puskesmas Goarie Subdistrict Marioriwawo Regency Soppeng. Method:This research is quantitative research that uses predictive correlation design. The sample in this research is taken by using purposive sampling technique. The sample estimation is 90 children under five. Result:Most of toddlers in this research have the normal weight (74.4%). The majority of growth aspects of toddler are in the normal category, including hard motor (84,5%), soft motor (87,8%), language and speech (73,3%), social personal (73,3 %) also interpretation at the end of toddler growth are in the normal category (66,7%). There is a significant relation between the weight of birth and the growth of toddler p=0,0001 smaller than α (0,05). Conclusion:The result of this research in Community Health Centre of Goarie Subdistrict Marioriwawo Regency Soppeng, showed that the majority of toddler born with normal birth weight and in the normal category, and there is a relation between the weight of birth with the growth of toddler. Health workers are expected to be screened to assess the growth of toddler and also parents are expected to care for childs’ growth.